Catálogo de las especies de la familia Pandalidae (Crustacea, Decapoda, Caridea) en Canarias - González Pérez, José Antonio; Caldentey, M.A.; Santana, J.I. (1990)
In the present paper, the presence of the fifteen species belong to the family Pandalidae (Crustacea, Decapoda, Caridea) in Canary Islands is discussed. An annotated catalogue of the shrimps of the Canary waters is given: Heterocarpus laevigatus, Plesionika edwardsii, Plesionika holthuisi, Plesionika ensis, Plesionika williamsi, Plesionika martia, Parapandalus narval and Parapandalus richardi. The first record of Plesionika holthuisi and Plesionika martia in Canary Islands is presented. En el presente trabajo se discute la presencia de quince especies pertenecientes a la familia Pandalidae (Crustacea, Decapoda, Caridea) en la islas Canarias. Se da un catálogo comentado de los camarones presentes en las aguas de Canarias: Heterocarpus laevigatus, Plesionika edwardsii, Plesionika holthuisi, Plesionika ensis, Plesionika williamsi, Plesionika martia, Parapandalus narval and Parapandalus richardi. Se cita por primera vez en aguas de Canarias la presencia de Plesionika holthuisi y Plesionika martia . 151 141 11